La Armonización De Los Impuestos Indirectos Según Las Decisiones 599 Y 600 De La Comunidad Andina - Caller Ferreyros, María E. (Revista de Derecho, 2019)
Decisions 599 and 600, were issue by the Andean Commission on 12 July 2004 and cameinto effect on 01 January 2008. Such Decisions, whose legal validity has been recognizedby the Andean Community Court, have as their object to achieve harmonizationof the legislation of member countries of the Andean Community –Perú, Colombia,Ecuador and Bolivia- which regulate aggregate value type and consumption taxes, inthe hopes that such imposition is neutral, that economic integration is facilitated andthat restrictions to intra-communitarian commerce are eliminated.For such effect, it is required that member countries comply with the transposition tonational law of the guidelines of indirect imposing foreseen by the quoted Decision,because, even when the principles of pacta sun servanda and the supremacy of internationallaw over internal law determine that treaties prevail over internal norms withthe range of laws, normative changes that are required in our country to implementDecision 599, should observe the constitutional principle of law reserve foreseen inarticle 74 of the Constitution.It is of upmost importance to know about the scope of Decisions 599 and 600, as wellas the aspects whose regulation differ in relation to the Law of General Sales Taxesand Consumption which governs our country. This will allow for the identificationof normative changes that the implementation of such Decisions should require, andwhen facing non-compliance from part of the State, the effects this will generate in thetax payers, who will be able to call for the direct application of the Decisions in thoseaspects which favor them (estoppel).
Keywords: Andean Community; Decisions; Harmonization; Andean Community Court; Aggregate Value Type Tax